Projecting future supply and demand for physical therapists in Japan using system dynamics. Issue 2 (June 2019) - Morii, Yasuhiro; Ishikawa, Tomoki; Suzuki, Teppei; Tsuji, Shintaro; Yamanaka, Masanori; Ogasawara, Katsuhiko; Yamashina, Hiroko
Highlights: Demand for physical therapists in Japan, the most aging country, is predicted. Demand for physical therapists will not increase after 2035 in Japan. Supply of physical therapist in Japan is projected using a system dynamic modeling. Scenario analyses reveal the effects of uncertainty or policy changes on the supply. Our research reveals a possible future oversupply of physical therapist in Japan. Abstract: Objectives: Japan is the oldest country in the world, and its demand for medical care is expected to increase. Although a clear vision regarding the supply and demand for physical therapy services is necessary, there has been no research that forecasts the supply and demand for physical therapists in Japan. Consensus has not been reached on whether the supply of physical therapists is sufficient. This study projects this supply and demand to provide medical policymakers with basic data. Methods: A system dynamics model was created to predict the number of physical therapists working in hospitals and clinics in Japan from 2014 to 2040. The future demand for physical therapy was estimated using the rehabilitation service utilization data from Open National Database, a publicly available nationwide health claims database. Sufficiency rates (supply/demand) were calculated, and sensitivity analysis was conducted on supply-related parameters. Results: The number of physical therapists was projected to be 1.74 and 2.54 times greater in 2025 and 2040, respectively, than in 2014. The sufficiency rates were 1.72, 2.39, and 3.30 in 2015, 2025, and 2040, respectively. The sensitivity analysis revealed that attrition rates had the greatest effects on sufficiency. Conclusions: Although the current supply appears to be needed, considering the expected increase and uncertainty in medical needs. However, there is a possibility of a future oversupply, especially after 2025, when the rate of increase in demand will lessen. Further studies are required to evaluate the distribution of physical therapists among regions and specialties.